Music education in the structure of teacher training in Chernihiv (early twentieth century) (Pedagogy of Higher and Secondary Education, 2013)
Matvienko S. I. Music education in the structure of teacher training in Chernihiv (early twentieth century).The article presents an historical analysis of the pedagogical training of teachers in Chernihiv province in the early twentieth century. Introduction to the scientific use of a wide range of archival documents revealed the particular use of church singing and music in the training of teachers of the province.
Keywords: Chernihiv; the system of teacher training; music; church singing schools